The Use of Multimedia in Chinese Language Teaching at Binus University - Fu Ruomei; Ma Feng (Humaniora, 2012)
Article outlines how multimedia is used in the classroom in the Chinese department of Bina Nusantara University. The Binusmaya system standardizes teaching and online communication. Multimedia is an effective supplement to traditional classroom based-teaching of Chinese. Multimedia can increase the learning motivation and improve teaching efficiency. Multimedia also plays a very important role in improving classroom based-teaching of Chinese, teaching standards and enhances a closer relationship between teachers and students.